The simplification of licensing procedure in job creation law: the effectiveness to attract foreign investor - Joko T. Suroso; Dani Durahman; Indra Budi (Cogent Social Sciences)
Foreign Direct Investment in Indonesia has a very significant role in realizing the economic growth as a developed country. It is important to provide a good quality investment climate for a developing country. However, there are existing challenges to attracting foreign investors. Several challenges include hyperregulations and overlapping authority. Referring to the Easy of Doing Business Indicator by the World Bank, Indonesia reformed its investment regulations together with other related regulations through Law No. 11 of 2020 on Job Creation. One of the main issues that is newly regulated is the simplification of the licensing process with an online risk-based approach. Even though it does not directly regulate corruption as the main obstacle for investment regarding the World Economic Executive Opinion Survey, the integrated online system for the entire licensing procedure could reduce corrupt practices within the process. This article describes the investment law reform and analyzes its effectiveness. The findings of this study have the potential to inform changes that must be made in the field of domestic investment law. The result shows that the legal framework reformation of the simplification of licensing through Job Creation Law theoretically reduces barriers and increases the interest of foreign investors to invest in Indonesia. Foreign investment is instrumental for Indonesia as a host state to increase its economy. to attract foreign investors, Indonesia has reformed the domestic investment law through the Job Creation Law. The stipulations that were revoked and revised were areas that can ease foreign investment in Indonesia based on the EoDB Indicators from the World Bank and the World Economic Forum’s Executive Opinion Survey. These reforms are simplification of licensing, licensing processes into one electronic licensing system, and harmonization of provisions through a risk-based approach. However, corruption as one of the main challenges to attracting foreign investors is not directly regulated in the Job Creation Law. It is hoped that the reform of the OSS and NSPK regulations mentioned above can prevent corrupt practices.